Structure and evolution of the squamate major histocompatibility complex as revealed by two Anolis lizard genomes - Card, Daren C.; Van Camp, Andrew G.; Santonastaso, Trenten; Jensen-Seaman, Michael I.; Anthony, Nicola M.; Edwards, Scott V. (Frontiers in Genetics, 2022)
The major histocompatibility complex (MHC) is an important genomic region for adaptive immunity and has long been studied in ecological and evolutionary contexts, such as disease resistance and mate and kin selection. The MHC has been investigated extensively in mammals and birds but far less so in squamate reptiles, the third major radiation of amniotes. We localized the core MHC genomic region in two squamate species, the green anole (Anolis carolinensis) and brown anole (A. sagrei), and provide the first detailed characterization of the squamate MHC, including the presence and ordering of known MHC genes in these species and comparative assessments of genomic structure and composition in MHC regions. We find that the Anolis MHC, located on chromosome 2 in both species, contains homologs of many previously-identified mammalian MHC genes in a single core MHC region. The repetitive element composition in anole MHC regions was similar to those observed in mammals but had important distinctions, such as higher proportions of DNA transposons. Moreover, longer introns and intergenic regions result in a much larger squamate MHC region (11.7 Mb and 24.6 Mb in the green and brown anole, respectively). Evolutionary analyses of MHC homologs of anoles and other representative amniotes uncovered generally monophyletic relationships between species-specific homologs and a loss of the peptide-binding domain exon 2 in one of two mhc2β gene homologs of each anole species. Signals of diversifying selection in each anole species was evident across codons of mhc1, many of which appear functionally relevant given known structures of this protein from the green anole, chicken, and human. Altogether, our investigation fills a major gap in understanding of amniote MHC diversity and evolution and provides an important foundation for future squamate-specific or vertebrate-wide investigations of the MHC.